Komunikasi Lintas Budaya dalam Islam - Baharuddin Baharuddin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
As God’s creatures that are unseparable and never standing alone, human beings will not be alienated from connections and communication between each other to strengthen themselves and their community. Business or ‘muamalah’ that have these functions are certainly not purely human thoughts, except from the instructions of God who created mankinds. Humans cannot simply be released to develop by therir own according to their own thoughts. There are limitations and rulesprovided by God as a fence so as not to get out of the nature of his creation. This paper discusses how God plays a role in communication with others and even with the universe. This role is explored and researched through His words which were revealed to His messengers to be conveyed to all mankind.